2017
DOI: 10.1155/2017/3514381
|View full text |Cite
|
Sign up to set email alerts
|

Drought Hazard Evaluation in Boro Paddy Cultivated Areas of Western Bangladesh at Current and Future Climate Change Conditions

Abstract: Drought hazard is one of the main hindrances for sustaining food security in Bangladesh, and climate change may exacerbate it in the next several decades. This study aims to evaluate drought hazard at current and future climate change conditions in theBoropaddy cultivated areas of western Bangladesh using simulated climate data from the outputs of three global climate models (GCMs) based on the SRES A1B scenario for the period between 2041 and 2070. The threshold level of Standardized Precipitation Evapotransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 38 publications
2
47
1
Order By: Relevance
“…The Penman-Monteith (PM) method is a commonly used approach recommended by the Food and Agriculture Organization of the United Nations to determine the potential evapotranspiration (PET) [59], and is considered by the International Commission on Irrigation and Drainage and American Society of Civil Engineers as the standard method for such calculations [60]. Combining the SPEI with the PM method was revealed to increase the reliability of results in arid areas of Northwest China [61]. As such, this method is applied in this study to calculate the PET given in Equation (A1).…”
Section: Appendix Amentioning
confidence: 99%
“…The Penman-Monteith (PM) method is a commonly used approach recommended by the Food and Agriculture Organization of the United Nations to determine the potential evapotranspiration (PET) [59], and is considered by the International Commission on Irrigation and Drainage and American Society of Civil Engineers as the standard method for such calculations [60]. Combining the SPEI with the PM method was revealed to increase the reliability of results in arid areas of Northwest China [61]. As such, this method is applied in this study to calculate the PET given in Equation (A1).…”
Section: Appendix Amentioning
confidence: 99%
“…Several studies have been conducted on drought assessment in Bangladesh and its impacts [11][12][13][14][15][16][17][18][19]. Most of these studies quantify drought severity by using the standardized precipitation index (SPI) [20], while very few studies have been conducted using the Palmer drought severity index (PDSI) [21] and the Standardized Precipitation Evapotranspiration Index (SPEI) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have attempted to investigate droughts in Bangladesh, most of them utilized weather information from a few stations without considering nationwide weather data. [15,16,18,19,31]. Only a handful of studies have utilized nationwide weather data by using mainly SPI indices [4,12,14,17,32].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that the overall monsoon rainfall will increase and post-monsoon rainfall will decreases in the future throughout most parts of the country [34,35]. Notably, very few studies have been done concerning future drought projections [35,36]. Islam et al [36] evaluated the drought hazards at current and future climate change conditions in the western region of Bangladesh by using simulated climate data from the outputs of three global climate models for the period between 2041 and 2070.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, very few studies have been done concerning future drought projections [35,36]. Islam et al [36] evaluated the drought hazards at current and future climate change conditions in the western region of Bangladesh by using simulated climate data from the outputs of three global climate models for the period between 2041 and 2070. Hasan et al [35] estimated the future drought conditions by using 25 km high resolution downscaled and projected climate data generated from the RCM known as PRECIS for a continuous period of 1971-2100.…”
Section: Introductionmentioning
confidence: 99%